Characterization of plant growth promoting rhizobacterial strain pseudomonas aeruginosa MCC 3877 with special reference to indole acetic acid (IAA) production - SOUMI BANERJEE; BIYAS MUKHERJEE; SIKHA DUTTA (International Journal of Pharma and Bio Sciences, 2019)
Several soil bacteria which flourish in the rhizosphere of plants,stimulate plant growth by different mechanisms, and are collectively known as Plant Growth Promoting Rhizobacteria (PGPR). PGPR not only improve plant growth but also increase nutrient mobilization, biocontrol of phytopathogens and production of phytohormones. The present study deals with isolation, characterization and identification of PGPR from rhizospheric soil of rice field of Burdwan district,W.B. Out of ten PGPR isolates, SB10 showed most remarkable plant growth promoting traits like phosphate solubilization, nitrogen fixation, hydrocyanic acid (HCN), ammonia, siderophore production along with eminent production of Indole Acetic Acid (IAA). SB10was identified as Pseudomonas aeruginosa by 16S rDNA sequencing method. Growth and IAA production of SB10 was measured at different time intervals and different L-tryptophan concentrations. SB10was found to produce copious amount of IAA in1.5% L-tryptophan supplemented media upto 48 hrs of growth. Efficacy of SB10 was measured in pot culture assay with rice seeds. Significant increase in growth parameters were observed in case of plant treated with SB10. Dry weight of shoot and root increased almost 13% and 22% respectively after 15 days.. So, these combined nature of the strain makes it suitable for application as phytostimulator, biofertilizer in agricultural fields for sustaining cultivation of crop.